Nutrition of marron, Cherax tenuimanus (Smith) under different culture environments : a comparative study. - Fotedar, Ravi (Curtin University, 1998)
Feeding trials were conducted to compare the nutritional requirements of juvenile marron (Cherax tenuimanus) under four different cultural environments. The rearing environments included aquaria under controlled laboratory conditions, cages in purpose-built commercial ponds, purpose-built earthen ponds and battery culture called the intensive crayfish culture system (ICCS).High levels of dietary cod liver oil in the semi-purified diet depressed the specific growth rates of juvenile marron under laboratory conditions. The dietary lipid levels were reflected in the lipid levels of the hepatopancreas of the marron. Dietary fatty acid profiles were also reflected in the fatty acid profiles of the hepatopancreas and subsequently in the tail muscles. Under cage environment in a purpose-built pond, dietary supplementation with cod liver oil (4%) plus sunflower oil (4%) increased the total biomass of juvenile marron. The specific growth rate under these condition had a strong positive correlation with all condition indices measured in the study (dry and wet hepatosomatic indices, dry and wet tail muscles to body weight ratio and moisture content of the hepatopancreas and tail muscles). The lack of protein in formulated practical diets, under commercial farm conditions, did not significantly influence the specific growth of juvenile marron but a diet containing fish protein source and fish oil resulted in a significantly higher survival. Feeding a diet containing fish protein and fish oil resulted in significantly higher wet tail muscles to body weight ratio than was observed with other diets. The inclusion of plant protein in formulated diets had an impact on the pond environment due to significantly higher ammonia levels that resulted in lower survival. Juvenile marron fed with a protein free diet and those fed with a plant protein diet had significantly lower protein levels in their hepatopancreas compared to those fed with diets containing animal protein. Juvenile marron in the battery culture environment tolerated long periods of starvation, utilising energy sources from the hepatopancreas and then from the tail muscles.Results from one rearing environment could not be directly transferred to another rearing environment. Environmental variables, particularly temperature, nitrogen metabolites and natural productivity of the ecosystem greatly influenced the nutritional requirements of the juvenile marron under culture. Ambient temperature and nitrogen metabolites may exert stronger control on the productivity, and thus profitability, of the commercial marron farms than the inclusion of micronutrients in the formulated diet.Specific growth rates, biomass, and wet and dry tail muscles to body weight ratios can be used as indicators of nutritional effectiveness of the diet. Further research is required to identify the interaction between the natural productivity of the ecosystem and the need to incorporate essential nutrients in formulated diets for the optimization of the marron production under commercial environment.